Role of social media in information-seeking behaviour of international students: A systematic literature review. Issue 5 (19th September 2016) - Hamid, Suraya; Bukhari, Sarah; Ravana, Sri Devi; Norman, Azah Anir; Ijab, Mohamad Taha
Abstract : Purpose: The purpose of this paper is to investigate the information-seeking behaviour of international students in terms of their information needs and to highlight the role of social media. Design/methodology/approach: In this paper, a systematic literature survey was conducted in order to investigate information-seeking trends among international students while using social media. As a result, an exhaustive systematic literature review (SLR) was carried out in order to investigate social media as a source for the observation of the behaviours of international students. For this purpose, 71 articles were selected from various well-known sources after an intensive SLR process of searching, filtering and enforcing the inclusion and exclusion criteria. Findings: As an outcome of this study, the information-seeking behaviour of international students was highlighted with respect to social media as a source of information. In addition, this research identifies the information needs of the international students and categorizes them by the roles played by the social media in fulfilling the information needs. Practical implications: A comparative study that highlighted the dearth of studies which merge the social media and information-seeking behaviour of international students as well as identify the future direction for the researchers and for benefits of international students. Originality/value: A detail SLR which highlights the need of shifting the information seeking behaviour from libraries to social media in regard to the new environment for international students.